ANALISIS CADANGAN DEVISA INDONESIA PERI0DE 1980-2000 (Dinamika Ekonomi, 2003)
ThemodelinthisresearchisreliabletoestimatethelnternationalReservebytheindependent variables.- iio* Linearity Test we conclude that the model has no spesificatione,ror or has no misspecification. The n sqrori is 98,87 % means that 98,87 %o change in theInternational Reserve can be affected by'CDP, Exchange Rate' Mon.ey. Supply an.d DornesticCredit. The rest ,o, b" .ortrtbited by tie other factors' B.ased on classical asumptions test' wefind that the made!;; i;"; i"^ o *rtti"ol,iiiiarity problem,^heteroscedasticityproblem andautocorrelation problem. From the ouryuj of Eviewi 3'0 we find the probability of F test isbelow than 0,05. k *",oin, that the tndipenient variables can affect the Interna.tional Reservesimultaneously. Then we find that alt sigpificance ^level.of independent variables are belowthan 0,05. It meuns inoiio,tnny thefactois can affect the International Reserve too'Keywords : International Reserve, classical Asumptions Test, The Error correction Mod'el